Uji Kandungan Fenol Dan Flavonoid Ekstrak Daun Seligi (Phyllanthus Buxifolius) Dengan Pelarut Etanol Dan Etil Asetat - Sunarmi, Sunarmi; Suhendriyo, Suhendriyo; Tri Ambarwanto, Sigit (Innovative: Journal Of Social Science Research, 2024)
Seligi leaves are traditionally used to treat sprains and reduce joint pain. The content of phenolic and flavonoid compounds in Seligi leaves also plays a role in its anti-inflammatory activity. Generally, phenolic and flavonoid compounds are soluble in polar and semi-polar solvents. This study aims to determine the levels of phenolic compounds and flavonoids in Seligi leaf extract. Seligi leaf simplicia was powdered with a fineness of 80 mesh and then extracted by maceration method using 96% ethanol and ethyl acetate. Each extract was tested for phenolic content quantitatively using the Folin-ciocalteu reagent with gallic acid as comparison, and the final result was expressed in terms of gallic acid equivalent by spectrophotometry at a wavelength of 731.5 nm. Determination of flavonoid levels using the UV-Vis spectrophotometry method with quercetin as a comparison at a wavelength of 435 nm. The results showed that the total phenolic content of the ethanol extract was 237.0 ± 9.4% mg GAE/g and that of the ethyl acetate extract was 12.8 ± 7.7% mg, GAE/g . Flavonoid content of ethanol and ethyl acetate extracts were 30.4 ± 9.5% mg QE/g and 10.5 ± 9.1% mg QE/g, respectively. Based on this, the content of phenol and flavonoid compounds was higher in extracts with ethanol solvent than ethyl acetate solvent.